1987
DOI: 10.1111/j.1439-0329.1987.tb01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the accelerated micromorphological degradation of epistomatal waxes in Norway spruce by motor vehicle emissions

Abstract: The epistomatal wax crystalloids of potted spruce plants exposed for 20 weeks to motor vehicle emissions along roadside and in a fumigation chamber were studied in the scanning electron microscope. An accelerated structural degradation of the wax crystalloids was observed in comparison with control plants. This structural degradation is considered to cause a structural obstruction of the stomatal antechambers and to contribute to the observed reduction of gas exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Because this structural wax degradation was highly accelerated in declining trees and because the shedding occurred when ca. 90 % of the stomates reached this stage of wax occlusion, it was concluded earlier that the physiological consequences of this structural impediment of stomatal gas exchange could be responsible for the premature senescence and shedding of needles (SAUTER and Voss 1986;SAUTER et al 1987).…”
Section: Discussionmentioning
confidence: 98%
“…Because this structural wax degradation was highly accelerated in declining trees and because the shedding occurred when ca. 90 % of the stomates reached this stage of wax occlusion, it was concluded earlier that the physiological consequences of this structural impediment of stomatal gas exchange could be responsible for the premature senescence and shedding of needles (SAUTER and Voss 1986;SAUTER et al 1987).…”
Section: Discussionmentioning
confidence: 98%
“…According to many reports the weathering of the epicuticular wax is due to atmospheric pollutants (HUTTUNEN and LAINB 1983;CROSSLEY and FOWLER 1986;SAUTER et al 1987;GRILL et al 1987;CAPE 1988;MANES et al 1988;FINK 1989;TURUNEN and HUTTU-NEN 1990). According to CAPE (1988) the "sensitivity" of the wax of the Pinus genus is greater than that found in Ahies alha Mill, and Picea ahies Karst.…”
Section: Pinus Pineamentioning
confidence: 99%
“…Micromorphological studies have been reported for conifer epicuticular waxes in relation to environmental factors since the start of the use of scanning electron microscopy technology. Air pollution has been shown to accelerate the degradation of needle waxes under field conditions (BERMADINGER et al 1987a,b;HUTTUNEN and LAINE 1983;CROSSLEY and FOWLER 1986;HAFNER 1986;SAUTER et al 1987;TRIMBACHER 1991). In fumigation experiments ozone, acidified rain or fog, alone, or in combination, caused similar symptoms on needles of Norway spruce and silver fir (MAGEL and ZIEGLER 1986;SCHMITT et al 1987;KRAUSE and CANNON 1991).…”
Section: Introductionmentioning
confidence: 99%